Skrining Risiko Cedera pada Atlet Basket Senior dengan Metode Functional Movement Screen (FMS) - Toriki, Naula Fauziah; Susanto, Indra Himawan; Sulistyarto, Soni; Bakti, Ananda Perwira (MAN Insan Cendekia Jambi, 2025)
Decline in functional movement quality often occurs with age, particularly in individuals aged 32-50 years, who begin experience reduced flexibility, stability and motor control. Risk of injury can assessed by identifying the presence of compensatory movements or a loss of functional balance during physical activities. One of tools used for this pipose in Functional Movement Screen (FMS), which is effective in predicting sport-related injuries. This study to evaluate FMS scores in this age group and identifity potential injury risk based on screening results. With quantitative design and Functional Movement Screen (FMS) for method. The study involved 12 participans aged 32-50 years, and must to do seven standard FMS test : Deep Squat, Hurdle Step, In-Line Lunge, Shoulder Mobility, Active Straight Leg Raise, Trunk Stability Push-Up, and Rotary Stability. The results showed that 10 participants scored ≤14 points, which fall into the high-risk category. 2 participans scored between 15-18 points. The avarage FMS score at senior basketball athletes was 13.08 (high-risk category). It’s mean imbalance muscle function between upper and lower body movements, which may increase the likelihood of injury particularly among older athletes. Therefore, FMS serves as valuable screening tool to identify injury prevention strategies in senior basketball players.